Analyzing microbes : manual of molecular biology techniques - Arora, Dilip K.; Das, Surajit; Sukumar, Mesapogu (Springer protocols, 2013)
This Springer Protocols manual offers authoritative practical guidance on applying key techniques in molecular biology to microbiological research, focusing on experimental protocols with stepwise instructions that make for easy laboratory reproduction